Ex-coal mine lands and their land suitability for agricultural commodities in South Kalimantan - S Sukarman; Rachmat Abdul Gani (Brawijaya University, 2020)
Coal mining is carried out with an open system that is dredging topsoil, and then taken the coal material. In 2016, the Indonesian Center for Agricultural Land Resources Research and Development conducted a survey, mapping and characterization of ex-coal mine areas in Tapin, Tabalong, Balangan, and Hulu Sungai Selatan regencies. This paper aimed to provide information based on the soil biophysical characteristics on ex-coal mine lands and to assess the land suitability for agricultural crops. The land characteristics obtained were then matched with the criteria of quality/suitability land for agricultural crops. The ex-coal mine lands in the four regencies cover an area of 17,141 ha. The landform characteristics have changed, namely voids and piles of excavated products in the form of small piles to hilly called anthropogenic landforms. According to Soil Taxonomy, the soil is classified as anthropic soil that was formed from material transported by humans, as Endoaquents Anthroportic, Epiaquents Anthroportic, and Udorthents Anthroportic. The heavy metals found were Pb, Hg, and Cd that varied from low to high uneven both vertically and horizontally. The land suitability class of Suitable (S) for dryland food crops, vegetable crops and forage crops covered 12,606 ha, while for annual crops covered 14,158 ha. The land suitability class is classified as Marginally suitable (S3), and the remaining as Not suitable (N). Based on the biophysical conditions, the ex-coal mine area requires considerable land reclamation and rehabilitation efforts, both for the restoration of soil chemical and physical properties.